Biochemical studies of cereal prolamins from sorghum and wheat - Miller, Christopher (Kansas State University, 2013)
Prolamins are the alcohol soluble storage proteins found in the endosperm of seeds from cereals and related grasses. The physical and biochemical properties of prolamins vary between species; and due to their relative abundance can greatly affect the properties and healthfulness of foods from those sources. In this work I investigate peptides from the high molecular weight glutenin of wheat, which is linked to dough elasticity and finished product quality. Using 2D NMR I determined the three-dimensional structure for the repeat peptide Ac- GQQPGQG-Am, which makes up ~50% of the 700 residue central domain. The structure was found to be a flexible β-hairpin with a type II β-turn across residues QPGQ. The NMR structure was later compared to 33 proteins with known three-dimensional structure carrying the exact sequence (backbone RMSD=0.802Å). This finding provides useful insight into the structure of high molecular weight glutenin and the molecular nature gluten elasticity. Alternatively, I studied the kafirin storage prolamins from sorghum, which do not have important physical properties, but are poorly digestible by humans and livestock. Improving digestibility of sorghum could significantly impact human health and nutrition in countries where sorghum is a dietary staple. In this work I devised a unique protocol to isolate kafirins under both non-reducing and reducing conditions. I studied kafirin extracts using SDS-PAGE, HPLC and MALDI-TOF MS, then purified β-kafirin, for the first ever characterization of this single protein. Past studies implicate β-kafirin as a source of poor digestibility due to extensive intermolecular disulfide cross-linking. Contrary to this claim I found more than 50% of β-kafirin was extractable without reducing agents. I used chymotrypsin to digest pure β-kafirin and map 10 cysteine residues to 5 intra-molecular disulfide bonds. Precise pairings have yet to be determined although the protein is largely intact after 12 hours of digestion. This work challenges us to think about sorghum protein body formation and the mechanism that leads to disulfide cross-linking during seed desiccation at maturity.
Keywords: Storage proteins; Sorghum; Wheat; Cereal prolaminsProlamins Kafirin; Agriculture, General (0473)